The Effectiveness of Post-Stroke Patient Care Education Intervention in Stroke Caregivers: A Literature Review - Rumiati, Rumiati -; Kariasa, I Made; Waluyo, Agung (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Educational interventions about stroke have been carried out by the health workers, one of which is by the nurse. However, the majority of the interventions focus more on the stroke patients than the stroke caregivers. Meanwhile, post-stroke patient care education interventions are urgently needed by the caregivers. Therefore, the author intends to review current literature about post-stroke patient care education interventions on stroke caregivers. Objective: This literature review aims to identify the effectiveness, methods, and impacts of daily care educational interventions for post-stroke patients on stroke caregivers. Methods: The method utilized was by analyzing online databases about the related topics from reputable sources.Â  Seven articles that met the inclusions criteria considering Randomized Controlled Trial (RCT) and Quasi-experimental design, time of publication, and English full text were obtained, and the results were presented. Result: Educational intervention could be carried out by several methods, including direct education at the patient's bedside, lectures followed by questions and answers, and booklets, home visits or telephone follow-up. Educational interventions could improve caregiver knowledge and skills in providing daily care for post-stroke patients, reduce burdens, reduce anxiety and improve the caregiver's quality of life. Educational interventions also positively impacted post-stroke patients, including improving the quality of life, functional abilities and the ability to do daily activities (ADL), reducing cognitive impairment, anxiety, and depression.Conclusion: Daily care education interventions for post-stroke patients can reduce the burden on the caregiver, either physical, psychological or social burdens.